Deletion of the Duffy antigen receptor for chemokines (DARC) promotes insulin resistance and adipose tissue inflammation during high fat feeding. (15th September 2018) - Benson, Tyler W.; Weintraub, Daniel S.; Crowe, Matthew; Yiew, Nicole K.H.; Popoola, Orishebawo; Pillai, Ajay; Joseph, Joel; Archer, Krystal; Greenway, Charlotte; Chatterjee, Tapan K.; Mintz, James; Stepp, David W.; et al.
Abstract: Objective: Inflammation in adipose tissues in obesity promotes insulin resistance and metabolic disease. The Duffy antigen receptor for chemokines (DARC) is a promiscuous non-signaling receptor expressed on erythrocytes and other cell types that modulates tissue inflammation by binding chemokines such as monocyte chemoattractant protein-1 (MCP-1) and by acting as a chemokine reservoir. DARC allelic variants are common in humans, but the role of DARC in modulating obesity-related metabolic disease is unknown. Methods: We examined body weight gain, tissue adiposity, metabolic parameters and inflammatory marker expression in wild-type and DARC knockout mice fed a chow diet (CD) and high fat diet (HFD). Results: Compared to wild-type mice, HFD-fed DARC knockout mice developed glucose intolerance and insulin resistance independent of increases in body weight or adiposity. Interestingly, insulin sensitivity was also diminished in lean male DARC knockout mice fed a chow diet. Insulin production was not reduced by DARC gene deletion, and plasma leptin levels were similar in HFD fed wild-type and DARC knockout mice. MCP-1 levels in plasma rose significantly in the HFD fed wild-type mice, but not in the DARC knockout mice. Conversely, adipose tissue MCP-1 levels were higher, and more macrophage crown-like structures were detected, in the HFD fed DARC knockout mice as compared with the wild-type mice, consistent with augmented adipose tissue inflammation that is not accurately reflected by plasma levels of DARC-bound MCP-1 in these mice. Conclusions: These findings suggest that DARC regulates metabolic function and adipose tissue inflammation, which may impact obesity-related disease in ethnic populations with high frequencies of DARC allelic variants. Highlights: DARC knockout mice fed high fat diet exhibited increased adiposity and weight gain. DARC knockout mice fed high fat diet exhibited impairments in glucose tolerance and insulin sensitivity. DARC knockout mice exhibited greater adipose depot inflammation.